Comparative politics : the problem of equivalence - Deth, Jan W. van. (London ; New York : Routledge, 1998)
This book tackles the issues involved and explores strategies to deal with many of the problems of establishing equivalence. Each contribution focuses on a theoretically relevant theme, such as: tolerance; political values; religious orientations; gender roles; voluntary associations; party organizations and party positions; democratic regimes, and the mass media. Each chapter covers different topics, methods, data and countries, making use of research to show the problems of finding similar or identical indicators in realistic research settings.
1. Equivalence in comparative political research / Jan W. van Deth -- 2. Tolerance / Bettina Westle -- 3. Political values / Ronald Inglehart -- 4. Religious orientations and church attendance / Martin Feldkircher -- 5. Gender roles / Michael Braun -- 6. Membership of voluntary associations / Jan W. van Deth and Frauke Kreuter -- 7. Party organisations / Thomas Poguntke -- 8. Party positions / Gábor Tóka -- 9. Institutional regimes / André Kaiser -- 10. Of readers, viewers, and cat-dogs / Rüdiger Schmitt-Beck.
Includes bibliographical references (pages 247-266) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Comparative government; POLITICAL SCIENCE -- Government -- Comparative; POLITICAL SCIENCE -- Reference; Comparative government; Vergelijkende politicologie; Institutions politiques comparées.